On the effect of molecular structure and composition on the photofragmentation of biomolecules - Levola, Helena (fi=Turun yliopisto|en=University of Turku|, 2016)
The research on the interaction between radiation and biomolecules pro-vides valuable information for both radiobiology and molecular physics. While radiobiology is interested in the damage inflicted on the molecule upon irradiation, molecular physics exploits these studies to obtain infor-mation about the physical properties of the molecule and the quantum me-chanical processes involved in the interaction. This thesis work investigated how a small change in the structure or composition of a biomolecule changes the response of the molecule to ioniz-ing radiation. Altogether eight different biomolecules were studied: nucleo-sides uridine, 5-methyluridine and thymidine; amino acids alanine, cysteine and serine; and halogenated acetic acids chloro- and bromoacetic acids. The effect of ionizing radiation on these molecules was studied on molecular level, investigating the samples in gas phase. Synchrotron radiation of VUV or soft x-ray range was used to ionize sample molecules, and the subsequent fragmentation processes were investigated with ion mass spectroscopy and ion-ion-electron coincidence spectroscopy. The comparison between the three nucleosides revealed that adding or removing a single functional group can affect not only the bonds from which the molecule ruptures upon ionization but also the charge localiza-tion in the formed fragments. Studies on amino acids and halogenated acetic acids indicated that one simple substitution in the molecule can dramatical-ly change the extent of fragmentation. This thesis work also demonstrates that in order to steer the radiation-induced fragmentation of the molecules, it is not always necessary to alter the amount of energy deposited on the molecules but selecting a suitable substitution may suffice.

Biomolekyylien ja säteilyn välisten vuorovaikutusprosessien tutkiminen on olennaista sekä säteilybiologialle että molekyylifysiikalle. Säteilybiologia tarkastelee säteilyn molekyyliin aiheuttamia vaurioita, kun taas molekyylifysiikka hyödyntää näitä tutkimuksia saadakseen tietoa molekyylin fysikaalisista perusominaisuuksista ja vuorovaikutusprosessien kvanttimekaanisista tapahtumaketjuista. Tässä väitöskirjatyössä tutkittiin, miten pieni muutos biomolekyylin rakenteessa tai koostumuksessa muuttaa molekyylin tapaa reagoida ionisoivaan säteilyyn. Tutkimuskohteiksi valittiin kahdeksan erilaista biomolekyyliä: nukleosidit uridiini, 5-metyyliuridiini ja tymidiini; aminohapot alaniini, kysteiini ja seriini; ja kaksi halogenoitua etikkahappoa, kloori- ja bromietikkahapot. Ionisoivan säteilyn vaikutusta näihin molekyyleihin tarkasteltiin molekyylitasolla tutkimalla näytemolekyylejä kaasufaasissa. Näytemolekyylit ionisoitiin VUV:n tai pehmeän röntgensäteilyn alueen synkrotronisäteilyllä, ja ionisaation jälkeistä molekyylin hajoamista tutkittiin ionien massaspektroskopialla ja ioni–ioni–elektroni-koinsidenssispektroskopialla. Kolmen nukleosidin vertailu paljasti, että yhden funktionaalisen ryhmän lisääminen tai poistaminen voi vaikuttaa paitsi siihen, mitkä sidokset molekyylissä katkeavat, myös siihen mihin muodostuneista hajoamistuotteista ionisaation tuottama sähköinen varaus jää. Aminohappojen ja halogenoitujen etikkahappojen tutkimukset puolestaan osoittivat, että pelkkä substituution vaihtaminen voi merkittävästi muuttaa molekyylin hajoamisen astetta. Tämä väitöskirjatutkimus myös osoittaa, että säteilyn aiheuttamaa molekyylin hajoamista voidaan hallita paitsi muuttamalla molekyylin kohdistuvan energian määrää, myös valitsemalla sopiva substituutio.